2020
DOI: 10.1101/2020.07.20.213298
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

S protein-reactive IgG and memory B cell production after human SARS-CoV-2 infection includes broad reactivity to the S2 subunit

Abstract: The high susceptibility of humans to SARS-CoV-2 infection, the cause of COVID-19, reflects the novelty of the virus and limited preexisting B cell immunity. IgG against the SARS-CoV-2 spike (S) protein, which carries the novel receptor binding domain (RBD), is absent or at low levels in unexposed individuals. To better understand the B cell response to SARS-CoV-2 infection, we asked whether virus-reactive memory B cells (MBCs) were present in unexposed subjects and whether MBC generation accompanied virus-spec… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
59
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(68 citation statements)
references
References 31 publications
9
59
0
Order By: Relevance
“…Intriguingly, the observed heterogeneity across sera in the competition experiment was suggestive of an increased prevalence of cross-reactive HCoV-OC43 antibodies (i.e., those whose binding could be at least partially competed with SARS-CoV-2 antigen) in the small set of paucisymptomatic individuals with confirmed SARS-CoV-2 infection compared with symptomatic patients with COVID-19. These data are consistent with previously published findings in SARS-CoV-1-infected patients (46) and recent reports describing immune responses to SARS-CoV-2 already present before the pandemic (47)(48)(49)(50). They also suggest that immunological phenomena often referred to as antigenic sin (51), i.e., the expansion of a preexisting memory response against partially homologous antigens of a related pathogen, might play a role in the progression from SARS-CoV-2 infection to full blown COVID-19 disease.…”
Section: L I N I C a L M E D I C I N Esupporting
confidence: 93%
“…Intriguingly, the observed heterogeneity across sera in the competition experiment was suggestive of an increased prevalence of cross-reactive HCoV-OC43 antibodies (i.e., those whose binding could be at least partially competed with SARS-CoV-2 antigen) in the small set of paucisymptomatic individuals with confirmed SARS-CoV-2 infection compared with symptomatic patients with COVID-19. These data are consistent with previously published findings in SARS-CoV-1-infected patients (46) and recent reports describing immune responses to SARS-CoV-2 already present before the pandemic (47)(48)(49)(50). They also suggest that immunological phenomena often referred to as antigenic sin (51), i.e., the expansion of a preexisting memory response against partially homologous antigens of a related pathogen, might play a role in the progression from SARS-CoV-2 infection to full blown COVID-19 disease.…”
Section: L I N I C a L M E D I C I N Esupporting
confidence: 93%
“…The S glycoprotein is proteolytically processed into two subunits: S1 (which contains RBD and the N-terminal domain [NTD]) and S2 (which mediates host-viral membrane fusion). S2 is the main target for pre-existing anti-S antibodies, consistent with its greater sequence conservation compared to S1, among HCoV species ( Anderson et al., 2021 ; Jaimes et al., 2020 ; Ng et al., 2020 ; Nguyen-Contant et al., 2020 ). While RBD is the main target for virus-neutralizing antibodies, responses to S epitopes outside of the RBD have been shown to have some neutralizing activity, for example, by binding to the S1 NTD, or by preventing protease cleavage or conformational changes required for entry into cells ( Chi et al., 2020 ; McCallum et al., 2021a ; Poh et al., 2020 ).…”
Section: Pre-existing Cross-reactive Immunity To Sars-cov-2mentioning
confidence: 56%
“…These pre-existing antibodies were more common in children and adolescents (Ng et al, 2020), suggesting a possibility that higher HCoV (common cold coronaviruses) infection rates in children than adults correlate with relatively less severe symptoms in children with COVID-19 (Castagnoli et al, 2020). In contrast, other studies have reported limited pre-existing cross-reactive antibodies against SARS-CoV-2 in unexposed individuals (Nguyen-Contant et al, 2020;Poston et al, 2020;Song et al, 2020). Specifically, only S2-targeted IgG antibody was detected and had some neutralizing activity, whereas anti-RBD IgG antibody was absent in unexposed individuals, though they found pre-existing cross-reactive memory B cells that were activated upon SARS-CoV-2 infection.…”
Section: Neutralizing Antibody and Cross-reactivitymentioning
confidence: 91%
“…Inversely, antibodies with neutralizing activity against SARS-CoV-2 isolated from COVID-19 convalescent individuals also cross-neutralize SARS-CoV and MERS-CoV . The degree of cross-reactivity between human coronaviruses (HCoVs) and SARS-CoV-2 has been widely studied but resulted in controversial findings (Anderson et al, 2021;Ng et al, 2020;Nguyen-Contant et al, 2020;Poston et al, 2020;. Using a flow cytometry-based method, SARS-CoV-2 spike protein-reactive antibodies have been detected in SARS-CoV-2-uninfected individuals (Ng et al, 2020).…”
Section: Neutralizing Antibody and Cross-reactivitymentioning
confidence: 99%